Analisis Kandungan Vitamin C Daun Kelor (Moringa oleifera Lam) Pada Ketinggian Berbeda di Kota Baubau - Sarni Sarni; Hasti Hamzah; Abdul Malik; Ida Ifdaliah A; Khadijah Khadijah (Universitas Khairun, 2020)
Moringa plants are one of the plants that contain lots of nutrients both minerals and vitamins. This study aims to determine the content of Vitamin C extract of Moringa oleifera Lam extract with different heights in Baubau. Moringa leaves were extracted by maceration using water and Sodium Oxalate (Na2C2O4) and vitamin C levels were analyzed using the UV-Vis Spectrophotometer Method. The results showed that the vitamin C content of Moringa leaves for a height of 20 masl (KP 20) in the coastal area was 0.59%, 50 masl (KM 50) 0.53%, while for an altitude of 296 masl (LBW) was 0.83% . From the data obtained shows that the highest levels of vitamin C are Moringa leaves located at a height of 296 mdl (LBW) compared to areas with low altitude in this case Moringa that grows on the coast (KP 20) and medium height (KM 50). From the results of this study it can be concluded that the vitamin C content of Moringa leaf extract which grows in the low area is 296.40 ppm, medium height 267,12 ppm and for the altitude region is 413.71 ppm.